Sistem Informasi Akuntansi Penjualan Umkm Berbasis Fintech (Studi Kasus Umkm Di Singaraja) - Muhamad Handika; Lucy Sri Musmini (Universitas Pendidikan Ganesha, 2021)
A research on the development of sales accounting information system of UMKM operation was neccesrily done in order to gain an accurate information as to the real condition of UMKM at a certain time. This study uses a descriptive approach in researching and analyzing the phenomenon of the UMKM industry. Support the growth of the UMKM operation. The approach of this study uses uses the scope of topic covering its width and depth,which is in the form of a case study. The subject of this study was UMKM join to Grab, and the object of the study was sales accounting information system of UMKM, that is, the UMKM itself becoming the the case study.The data of this study were collected through direct observation and interview. The data that had been collected were annalysed qualitatively, which resulted in a desciption of sales accounting information systemof UMKM that had been developed. From the analysis of the data, it can be concluded that: the sales accounting information system possed by the UMKM is currently very simple and not systematic yet. Viewed from the information obtained as well as from the current documents of the UMKM, the manager does not know well about the development and the working system of his business.The sales accounting information system of the UMKM needs to be organised in a much better way, so that the business can provide information about the sale, cash input, cash output, supply, sale capital prize, and gross benefit for each period. Then, if the manualsystem has been designed with adequate information output, the computer-based system can be made. In the computer-based sales accounting information system, the staff is only concerned with entering the input, an then the program will process the data being entered. At last, automatically the output than can be used as the basis for decision making by the manager can be obtained.